Parental Mediation in Parenting 4.0: A Qualitative Case Study on Early Childhood Digital Literacy in Indonesia - Bambang Winarji; Upik Elok Endang Rasmani; Novita Eka Nurjanah; Jumiatmoko Jumiatmoko; Nurul Shofiatin Zuhro; Anjar Fitrianingtyas (AL-ISHLAH: Jurnal Pendidikan, 2026)
Rapid digital advancement presents both opportunities and challenges for young children, necessitating effective parental mediation to support early childhood digital literacy. This study investigates the implementation of Parenting 4.0 at RA STIBA Azkiya, an Islamic early childhood education institution, in fostering children’s digital competencies. A qualitative single-case study design was employed involving 11 participants (six parents, four teachers, and one principal). Data were collected through semi-structured interviews, observations, and document analysis, and analyzed using Miles and Huberman’s interactive model. Digital literacy was conceptualized as encompassing operational skills, informational awareness, digital safety, and guided critical thinking mediated by adults. The findings indicate that Parenting 4.0 practices—such as introducing basic digital tools, supervising screen time, selecting age-appropriate content, facilitating parent–child dialogue, and modeling responsible digital behavior—were associated with children’s ability to use digital devices safely and meaningfully. These practices were further supported by institutional mechanisms, including monitoring books, workshops, and parent consultations, which reinforced consistent parental engagement. This study provides a context-specific account of how Parenting 4.0 is operationalized through defined parental roles and institutional support within an Islamic early childhood setting, contributing to the literature on parental involvement in digital literacy. However, the single-site and culturally specific context limit generalizability. Future research should examine Parenting 4.0 across diverse educational settings to enhance comparative understanding of early childhood digital literacy.